Studi Instrumen Streaming Current Monitor sebagai Kontrol Koagulan pada Instalasi Pengolahan Air Minum Sadu Soreang - Tri Septia, Fakhri; Mohamad Rangga Sururi (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The streaming current monitor (SCM) is an instrument used to measure small particles suspended in water and ensure their stability. It can be operated in real time to detect changes in water quality and temperature. The SCM provides a continuous flow that can quickly and accurately measure changes in water quality. In the Water Treatment Plant (WTP), it supplements conventional laboratory tests, enabling longer testing times and reducing the cost of chemical materials. The SCM also provides real-time data analysis which is logged in the Supervisory Control and Data Acquisition (SCADA) system. Integrating this technology reduces the need for manual decision-making and minimises human error, offering flexibility and control to operators. SCM technology was developed at IPA Sadu in Soreang to improve operational efficiency. It also uses other real-time monitoring instruments, such as those measuring pH, turbidity and chloride. These instruments are integrated into the SCADA data management system, enabling data collection and monitoring of potential issues and enhancing the efficiency and accuracy of the water quality control process.